Para-Azaquinodimethane based quinoidal polymers for opto-electronic applications: impact of donor units on the opto-electronic properties. Issue 17 (28th July 2022) - Dyaga, Bharath; Mayarambakam, Sasikumar; Ibraikulov, Olzhas A.; Zimmermann, Nicolas; Fall, Sadiara; Boyron, Olivier; Heiser, Thomas; Leclerc, Nicolas; Berton, Nicolas; Schmaltz, Bruno
Abstract : para -Azaquinodimethane ( p -AQM) based quinoidal–donor (Q–D) polymers have been synthesized following a strategy for enhancing the backbone planarity and control the bond length alternation (BLA). Abstract : para -Azaquinodimethane ( p -AQM) based quinoidal–donor (Q–D) alternating copolymers offer a unique opportunity to investigate the properties of quinoidal polymers. It was however reported that the bandgap increases with increasing number of donor aryl units, as a result of a weakening of the quinoidal character of the polymer backbone. To overcome this issue, herein two new polymers were designed and synthesized by incorporating fused donor (PAQM2T-TT) and vinylene linker (PAQM2T-TVT) units, following a strategy for enhancing the backbone planarity. The thiophene-containing polymers PAQM3T and PAQM4T were also synthesized for better understanding of the influence of structural variations. Thus, in comparison with PAQM3T and PAQM4T, PAQM2T-TT and PAQM2T-TVT exhibited a slight red shift in spite of having more extended donor units, which is consistent with enhanced planarity and quinoidal character as suggested by DFT calculations. It is also found that the different donor units have a limited impact on the HOMO energy level of the p -AQM copolymers. Transport properties are measured by field effect transistors, and the photovoltaic properties of these p -AQM based polymers are reported for the first time, as electron donor materials in inverted configuration devices. PAQM2T-TVT and PAQM2T-TT exhibit a planar structure leading to a hole mobility of respectively 3.8 × 10 −2 cm −2 V s −1 and 1.7 × 10 −2 cm −2 V s −1 . When combined with a fullerene acceptor in solar cells, the PAQM2T-TT polymer exhibited a highest PCE of 2.32%.